Binding of gephyrin to microtubules is regulated by its phosphorylation at Ser270 - Zhou, Lin; Kiss, Eva; Demmig, Rebecca; Kirsch, Joachim; Nawrotzki, Ralph; Kuhse, Jochen (Histochemistry and cell biology, 2021)
Gephyrin is a multifunctional scaffolding protein anchoring glycine- and subtypes of GABA type A- receptors at inhibitory postsynaptic membrane specializations by binding to the microtubule (MT) and/or the actin cytoskeleton. However, the conditions under which gephyrin can bind to MTs and its regulation are currently unknown. Here, we demonstrate that during the purification of MTs from rat brain by sedimentation of polymerized tubulin using high-speed centrifugation a fraction of gephyrin was bound to MTs, whereas gephyrin phosphorylated at the CDK5-dependent site Ser270 was detached from MTs and remained in the soluble protein fraction. Moreover, after collybistin fostered phosphorylation at Ser270 the binding of a recombinant gephyrin to MTs was strongly reduced in co-sedimentation assays. Correspondingly, upon substitution of wild-type gephyrin with recombinant gephyrin carrying alanine mutations at putative CDK5 phosphorylation sites the binding of gephyrin to MTs was increased. Furthermore, the analysis of cultured HEK293T and U2OS cells by immunofluorescence-microscopy disclosed a dispersed and punctuated endogenous gephyrin immunoreactivity co-localizing with MTs which was evidently not phosphorylated at Ser270. Thus, our study provides additional evidence for the binding of gephyrin to MTs in brain tissue and in in vitro cell systems. More importantly, our findings indicate that gephyrin-MT binding is restricted to a specific gephyrin fraction and depicts phosphorylation of gephyrin as a regulatory mechanism of this process by showing that soluble gephyrin detached from MTs can be detected specifically with the mAb7a antibody, which recognizes the Ser270 phosphorylated- version of gephyrin.